Effects of growth promoters on sheep metabolism and growth - Al-Doski, Shaker (2015)
The aim of this thesis was to investigate the mechanisms that mediate the effects of beta-adrenergic agonists (BA) and Growth Hormone (GH) in sheep, by examining the changes in skeletal muscle transcriptome and blood metabolome in order to identify the predominant metabolic mechanisms by which muscle hypertrophy was mediated. Male lambs (120 days old) were all fed a high protein/energy feed ad-libitum, with the GH group (n=10) receiving a single subcutaneous injection of bovine GH (3.75mg/kg body weight, POSILAC, Monsanto) on day 1; the BA group (n=10) receiving BA (cimaterol) at 10mg/kg feed, whereas the control group (CO, n=11) only had the ad-libitum feed. After 6 days sheep were slaughtered, plasma and samples of the Longissimus dorsi (LD), Supraspinatus (SS) muscles and liver were collected. The effect of treatments on the LD transcriptome was assessed on a subset of samples (n=3 from each treatment) via a cross-species approach using the Affymetrix Human U133+2 GeneChip array (47K human microarray). Verification of identified differentially expressed genes and proteins was by quantitative RT-PCR or western blotting, respectively, on all animals. Metabolomics analysis of plasma samples was carried out by Metabolon Inc. (USA) using GC/MS and LC/MS/MS platforms. BA, but not GH, significantly (P<0.05) increased muscle weights and this was associated transition to large fast-glycolytic muscle fibre types. In GH, but not BA treated animals, there was an increase in liver weights (P<0.001). This was associated with an increase in the whole liver content of glycogen (P<0.001), protein (P<0.01), and lipid (P<0.05) content. Analysis of the LD transcriptome of the treated sheep identified 477 and 316 transcripts were significantly altered (P<0.05 and 1.5 fold change) by BA and GH respectively, relative to controls. This muscle was selected as it is a commercial valuable muscle and is commonly used for muscle biochemical studies therefore this would allow us to make comparisons to other studies, including our own. In addition it is a fast glycolytic muscle fibre type there could be compared against SS muscle (oxidative muscle fibre type). BA decreased the expression of genes involved with oxidative phosphorylation and upregulated those serine biosynthetic pathways. Subsequent qRT-PCR analysis showed a BA induced increase in expression of phosphoglycerate dehydrogenase (PHGDH) (P<0.05) and phosphoserine-aminotransferase (PSAT) (P<0.05) mRNA in both LD and SS but not liver. In LD there was also an increase (P<0.001) in PHGDH protein in muscle from BA treated sheep relative to GH treated sheep. Up-regulation of this pathway has been previously reported in cancer cells which has a tendency to be associated with an increase in gene expression of a specific isoform of the glycolysis enzyme pyruvate kinase (PKM2) which has reduced activity. Total PKM and PKM1 and PKM2 isoforms were increased in the SS and LD of BA treated sheep (P<0.05). Previous studies in cancer cells have suggested that increases in serine synthesis are mediated by changes in PKM2 expression and associated enzyme activity. The lack of a differential increase in PKM2 suggested that the regulation of muscle PK in BA treated animals was not critical to the potential increase in serine synthesis capacity. No clear change in PKM gene expression suggested this was not the mechanism by which the serine synthesis pathway was stimulated. There was an increase (P<0.05) in the expression the mitochondrial form of phosphoenolpyruvate carboxykinase (PCK2) in the LD of BA treated sheep, which might be expected to increase gluconeogenic potential thereby increasing intermediates that could be used for serine synthesis. There was no effect of this gene on sheep treated with GH. An increase in the gene expression of asparagine synthetase (ASNS) was also seen in the muscles of BA but not GH treated sheep (P<0.001) and there was no effect on their livers, which further suggested that BA was influencing the production of nonessential amino acids. Metabolomics analysis showed that products of triacylglycerol breakdown, glycerol and free fatty acids, were all elevated in the plasma of both BA and GH treatments, indicating lipolytic effects but the increase in the free fatty acid profile were more pronounced with GH treatment (P<0.05). Likewise GH rather than BA had a greater impact on elevating plasma glucose and associated metabolites such as pyruvate (P<0.05). There was no effect of either treatment on plasma serine or asparagine concentrations. However there was a decrease in glycine (P<0.05) and glutamine (P<0.05) in GH relative to control, with BA decreasing histidine (P<0.05) and methionine (P<0.01) relative to control. Cell culture experiments were carried out in the myogenic C2C12 cell line to determine if the genes associated with the GH and BA response in sheep were affected during myogenesis and whether there was an effect of des (1-3) IGF-I and dibutyryl cyclic adenosine monophosphate (dbcAMP) that stimulates GH and BA signalling pathways respectively. During differentiation, without treatment, gene expression of PHGDH and PSAT enzymes declined (P<0.05), which might be expected as cells move from a proliferative to a terminally differentiate state. There was no clear effect of treatment on genes associated with the serine synthesis pathway suggesting that the effects of BA, in particular, are on muscle fibres rather than differentiating cells. Of the two growth promoters examined in this thesis BA appears to be the most potent in skeletal muscle. A clear effect of this agent was an increase in the gene expression of the serine biosynthetic pathway, which has been shown to be upregulated in various cancers and, in this pathology, is thought to be a novel mechanism for hyperplastic growth. The associated changes in the expression of genes such as ASNS and PCK2 indicate that their co-ordinated upregulation could be mediated via endoplasmic reticulum stress response mechanisms. Unlike GH, BA does not appear to have a major effect upon the systemic mobilisation of nutrients, but instead seems to targets muscle fibres, activating muscle biosynthetic pathways that potentially provide the substrates required for growth.